In Silico Exploration of Suruhan Leaves (Peperomia pellucida) for Triple-Negative Breast Cancer Therapy Targeting AURKA - Rovik, Anwar; Andyra, Vania Uly; Afifah, Laelatul (Journal of Experimental and Clinical Pharmacy (JECP), 2024)
Breast cancer is the most common type of cancer worldwide. One of the most widely used chemotherapeutic agents in the treatment of breast cancer is doxorubicin. However, doxorubicin has been reported to cause side effects. Suruhan (Peperomia pellucida) contains bioactive compounds that might protect against breast cancer cells. This study aims to analyze the bioactive compound activity of Suruhan leaves in triple-negative breast cancer in silico. The study was conducted by reviewing published literature on bioactive compounds in Suruhan leaves, predicting the protein target, analyzing the gene expression in triple-negative breast cancer (TNBC) patients, analyzing the protein interactions, and examining patient survival. There are five common bioactive compounds in Suruhan leaves, including peperomin A; 6,8-dihydroxy kaempferol 3,6,7,4'-tetramethyl ether 8-neohesperidoside; dillapiole; carotol; and pellucidin A. AURKA is a target protein for bioactive compounds that are also overexpressed in TNBC patients. AURKA has strong interactions with many proteins, including TPX2, NEDD9, CCNB2, CDC20, PLK1, BIRC5, INCENP, TACC3, TP53, and MYCN. The AURKA has emerged as a promising target for TNBC therapy.